Tough on Hate? : The Cultural Politics of Hate Crimes - Lewis, Clara S., 1981- (Book collections on Project MUSE., 2014)
Tough on Hate is the first book to examine the cultural politics of hate crimes both within and beyond the law. Drawing on a wide range of sources, including personal interviews, unarchived documents, television news broadcasts, legislative debates, and presidential speeches, the book challenges readers to reconsider their understanding of hate crimes and raises startling questions about the trajectory of civil and minority rights.